(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
The development of didactics linked to acts of creation and the work of sensitive exploration in the body and thought from the collective, seeks to enhance the creative processes of the members of the Backú Artistic Collective, to generate a montage of research - creation that speaks of the ruana as a symbol of the prevalence of the Cundiboyacense peasant. Starting from creation laboratories that put into practice the method of collective creation proposed by Enrique Buenaventura and Santiago García. The collection of information is made from the audiovisual, sound and photographic record in each of the laboratories and in the research that is carried out against the sociocultural context of the ruana, object of creation, additionally elaboration of ethnographic and phenomenological interviews that collect the experiences of the Cundiboyacense peasant and of the artists - creators of the collective, the documentation of the information is carried out through field logs, organized by categories that serve for the analysis and understanding of the lines of research of the Master’s degree in education of the UAN and the Master in artistic studies of the ASAB, in this way, art and education are put into dialogue to understand what happens within the creation processes.